ANALYSIS OF THE QUALITY OF FINAL ASSESSMENT PROBLEMS OF SEMESTER I LP MAARIF DUKUN DISTRICT IN ENGLISH COURSES FOR 2022/2023 ACADEMIC YEAR USING WINSTEP SOFTWARE ANDITEM AND TEST ANALYSIS (ITEM) 4.3) - Fajriati, Nita - (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
Analysis of the items needs to be done as a repair and refinement of the items. So that the preparation of the questions is in accordance with predetermined indicators which are really shown as their function is as a measuring tool for student learning outcomes. The type of research conducted in this research is descriptive quantitative research. The data analysis technique uses classical theory assisted by Iteman software and the Rasch model with the winstep program. This research is focused on examining the basic concepts of classical theory which are translated into important matters including validity. Reliability, item difficulty level, and item discrimination. The results of the research conducted showed that the quality of the items based on classical theory using the iteman and the Rasch model using the winstep application obtained a reliability value with the classical theory of 0.882 which was generally categorized with high reliability so that it could be said that the questions were reliable, whereas in the analysis using the rasch model obtained results of 0.85 with the reliable category. So it can be concluded that based on the results of the analysis of the questions using classical theory and the Rasch model, the questions are said to be reliable and in a good category.